DRIVING SUSTAINABLE PERFORMANCE : THE ROLE OF GREEN ENTREPRENEURIAL ORIENTATION AND INNOVATION CAPABILITY AMONG SMES - Dedi Joko Hermawan; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (JURNAL PROFIT, 2025)
Sustainability performance in micro, small, and medium enterprises (MSMEs) is a crucial element for strengthening regional economic competitiveness, including in Probolinggo City. Government policies that encourage business sustainability through capacity enhancement, innovation, adaptation, and the reinforcement of green entrepreneurial orientation position entrepreneurial orientation and innovation capability as strategic determinants of MSME continuity. Global demands related to environmental issues, advances in production technology, shifting consumer preferences, and the growing need for eco-friendly products increasingly require MSMEs to develop their innovation capabilities. Although most MSMEs have not yet attained the level of innovation capability and green entrepreneurial orientation found in larger enterprises, the demand to operate sustainably remains a priority. This study aims to analyze the relationship between green entrepreneurial orientation, innovation capability, and sustainability performance among MSMEs in Probolinggo City. The research involved 30 MSME actors as respondents, using questionnaires as the primary instrument and data processing through SmartPLS. The findings indicate that green entrepreneurial orientation has a positive and significant effect on innovation capability and sustainability performance. Innovation capability also significantly influences sustainability performance; however, it does not mediate the relationship between green entrepreneurial orientation and sustainability performance.